Strategies for Sustainable Development of Companies in International Markets in the context of Digitalization - Tanasiichuk, Alona; Mykhailyshyn, Liliia; Fedoryshyna, Larysa; Lagodiienko, Volodymyr; Tetyana, Ruda; Polyova, Nataliya; Yurchenko, Oksana (European Journal of Sustainable Development, 2024)
The war conditions are forcing Ukrainian wood processing companies to review their strategies and identify new opportunities in international markets. It is important to develop business regardless of the circumstances: to be able to adapt to any conditions, whether it is a lack of resources or limited opportunities. The key aspect now is to create sustainable strategies that will allow Ukrainian companies to be flexible and competitive in international markets, strengthening their position regardless of the circumstances. Sustainable strategies for wood processing companies in international markets are becoming a key success factor in the conditions of modern globalization. The use of digital tools can help improve the efficiency of Ukrainian wood processing companies and provide them with competitive advantages. Digital tools allow for collecting and analyzing large amounts of data about the audience, competitors, and the market in general, which helps to understand consumer needs better, predict market trends, and adapt strategies accordingly. Digital tools also help to improve communication between wood processing companies and international partners and increase interaction with them. The study confirmed that collecting and analyzing data on potential customers and their requirements is a key step in entering new international markets. Modern digital tools greatly simplify this process, enabling fast and efficient collection, analysis, and interpretation of large amounts of data. They can provide useful insights into consumer behavior, preferences, and demand for certain goods and services. These digital tools have made it possible to process large amounts of data to prepare Ukrainian forestry enterprises for international markets. International marketing research is crucial for the successful development of an enterprise's strategy at the international level. The markets of Poland, Germany, Austria, Italy, and Ukraine were analyzed to compare various indicators. The expert evaluation was used to calculate the scores for each market, which allowed us to determine which ones are the most attractive for Ukrainian companies specializing in wood processing and creating added value in the domestic market. The study showed that in the current environment, it is possible to increase exports of product subgroups "4407 Timber", "4408 Cladding sheets" and "4415 Cases, boxes" to the markets of Germany, Austria, and Italy. This will help many Ukrainian enterprises to resume their business activity during the second year of the war and in the post-war period. Keywords: advanced digital tools, international business operations, plan for sustainable development, a set of metrics measuring the appeal of international markets, networking platforms, international market, businesses